Nutrient Management Drives the Direction and Magnitude of Nitrous Oxide Flux in Crop Residue-Returned Soil Under Different Soil Moisture - Lenka, Sangeeta; Choudhary, Rajesh; Lenka, Narendra Kumar; Saha, Jayant Kumar; Amat, Dolamani; Patra, Ashok Kumar; Gami, Vijay; Singh, Dharmendra (Frontiers in Environmental Science, 2022)
Crop residue, a key organic carbon input, has the potential for soil carbon sequestration. However, previous studies have shown an inconsistent effect of residue return on the direction and magnitude of soil nitrous oxide emission. We used a laboratory-based soil incubation to test the response of nitrous oxide (N2O) emission to crop residue type, soil moisture, and how nutrient management modulates these responses. In this study, we incorporated crop residues with different qualities (wheat, rice, soybean, and maize) at two soil moisture {80% field capacity (FC) and 60% FC} and under seven nutrient levels: N0P0K0 (no nutrients), N0PK, N100PK, N150PK, N100PK+manure@ 5 Mg ha-1, N100PK + biochar@ 5 Mg ha-1, N150PK+ biochar@ 5 Mg ha-1. The results demonstrated significant (p<0.01) differences in the magnitude of N2O emissions among treatments. However, only the interaction effect of residue x nutrient and nutrient x moisture was significant (p<0.05). Residue effects were negatively correlated with C: N ratio, and a strong positive correlation (p<0.01) was obtained between N2O emission and CO2 respiration, labile carbon, mineral N, and residue total nitrogen. The addition of residues (cf. control soil) without nutrients significantly increased N2O emissions. However, cumulative fluxes of N2O decreased by 6 to 17% when maize and wheat residues (cf. control soil) were applied with nutrients. Negative fluxes of N2O indicating consumption were observed in every treatment after 57 days of incubation and were most pronounced in control soil without residue and nutrients. Decreasing the soil moisture from 80% FC to 60% FC, the N2O consumption rate increased by 6.6 times across residue types and nutrient management. Our results demonstrated that soil CO2 respiration, nitrate N, labile SOC, and residue TN are key predictor variables of N2O emission pathways in residue returned soils. The results suggested that nutrient addition could alter the magnitude and direction of soil N2O flux by residue type and soil moisture through influencing the underlying soil microbial processes of the C and N cycle in Vertisol of subtropical India.